2019
DOI: 10.1136/lupus-2019-000331
|View full text |Cite|
|
Sign up to set email alerts
|

Cervus and cucumis peptides ameliorates bone erosion in experimental arthritis by inhibiting osteoclastogenesis

Abstract: ObjectiveRheumatoid arthritis is an autoimmune disease characterised by inflammation and bone loss, leading to joint destruction and deformity. The cervus and cucumis polypeptide (CCP) injection, one of the traditional Chinese medicine injections combined extracts from deer horn and sweet melon seeds, is widely used to treat arthritis and bone fracture in China. The present study investigated the therapeutic efficacy and mechanism of CCP on pathological immune cells and bone homoeostasis in rodent experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Moreover, it was revealed previously (Alves et al, 2016;Kamel et al, 2019) that RANKL pronounced expression in the positive control (FCA induced untreated rat) group whereas, treatment with MTX and bioactive components downregulated the RANKL gene expression, thus playing a protective role in bone erosion. The mRNA expression level of RANKL significantly increased in FCA induced positive control group whereas, the mRNA expression of OPG significantly reduced at the time of arthritis onset (Kishimoto et al, 2004;Lin et al, 2019), the same trend is observed in current research in which positive control group showed marked elevation in the expression level of RANKL, that is reverted back to its normal via walnut based treatments. The drug MTX is commonly used in the treatment of RA.…”
Section: However Interventions Involving Variable Doses Of Ethanol Andsupporting
confidence: 84%
“…Moreover, it was revealed previously (Alves et al, 2016;Kamel et al, 2019) that RANKL pronounced expression in the positive control (FCA induced untreated rat) group whereas, treatment with MTX and bioactive components downregulated the RANKL gene expression, thus playing a protective role in bone erosion. The mRNA expression level of RANKL significantly increased in FCA induced positive control group whereas, the mRNA expression of OPG significantly reduced at the time of arthritis onset (Kishimoto et al, 2004;Lin et al, 2019), the same trend is observed in current research in which positive control group showed marked elevation in the expression level of RANKL, that is reverted back to its normal via walnut based treatments. The drug MTX is commonly used in the treatment of RA.…”
Section: However Interventions Involving Variable Doses Of Ethanol Andsupporting
confidence: 84%
“…[ 14 ] They inhibit the inflammatory response, reduce the content of tumor necrosis factor-alpha (TNF-alpha) in serum, [ 15 ] and assist macrophage-derived cytokines to play a role in tissue repair. [ 16 ] According to the pathogenesis of RA in traditional Chinese and western medicine, UC-MSCs are pre-stimulated by the polypeptide of LG to promote the superposition of kidney-nourishing, bone strengthening, blood-activating, and collateral-opening, and also reduce the release of pro-inflammatory factors. While stabilizing the internal environment, the biological characteristics of UC-MSCs migration, homing, regeneration, repair, and immune regulation can be enhanced, which also conform to the principle of specimen co-treatment in traditional Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%
“…LG contains TGF‐β, which assists macrophage‐derived cytokines in tissue repair. [ 80 ] In addition, it inhibits inflammatory response and reduces TNF‐α levels in the serum. [ 80 , 81 ] In vitro, the secretion of anti‐inflammatory factors, such as HGF, PGE‐2, and TNF, was remarkably increased in the LG‐treated MSCs group.…”
Section: Inhibition Of Inflammationmentioning
confidence: 99%